PENGARUH MODEL KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA PADA MATA PELAJARAN IPAS KELAS IV UPTD SDN 1 KEDOKANBUNDER - Tobroni; Piyantina Rukmini; Daryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low learning outcomes of students and the ineffectiveness of learning models in science subjects make students less active in learning, which is the background for the preparation of this study. This study aims to determine the effect of the two stay two stray cooperative learning model on learning outcomes and student activity in grade IV of UPTD SDN 1 Kedokanbunder. This study uses an experimental method with a pretest posttest control group design. The population of the study was all students of UPTD SDN 1 Kedokanbunder with a sampling technique using random sampling. The research sample consisted of 60 students who were students in grades IV A and IV B. Research data were collected through multiple choice tests and observation sheets. Data analysis was carried out using the independent sample t test with the help of SPSS. Based on the results of the study using independent sam ple t, the calculated ˃ (9.542 ˃ 2.001) and sig. (2-tailed) 0.000 ˂ 0.05 were obtained, so was rejected and was accepted. Meanwhile, the results of the independent sample t test on student activity showed that the lower and upper values ​​were each negative, namely lower = -0.875 and upper = -0.205, while sig. (2-tailed) was 0.003 ˂ 0.05, so it is said that the data in the table above shows that is rejected and is accepted. Thus, it can be stated that the cooperative model type two stay two stray can affect the learning outcomes and student activity in class IV UPTD SDN 1 Kedokanbunder.